On the relative efficiency of purified diets, with variable protein levels, in young catfish, Heteropneustes fossilis Bloch - Firdaus, S (Indian Journal of Fisheries, 2011)
A 4-week feeding experiment was conducted on [eteropneustesjossilis to work out the relative efficiencies of purified diets with 3 different levels of protein. Fish fed with 40% protein diet gave the maximum growth and best conversion efficiency. The growth of fish was low both at 20% and 60% protein in the diet. Changes observed in the proximate composition were related to the fish growth.